The light we give : how Sikh wisdom can transform your life - Singh, Simran Jeet (Riverhead Books, 2022)
"As a boy growing up in South Texas, Simran Jeet Singh and his brothers confronted racism daily. Instead of giving in to negativity, he delved into the Sikh teachings he grew up with and embraced the lessons to seek the good in every person and situation and to find positive ways to direct his energy. Part memoir, part spiritual journey, The Light We Give offers an approach to a happier, more fulfilling life through Sikh teachings on love and service"--